Yield and Composition of the Essential Oil of the Opopanax Genus in Turkey - Babacan, Ebru Yuce; Demirpolat, Azize; Cakilcioglu, Ugur; Bagci, Eyup (Mdpi, 2023)
The genus Opopanax W. Koch (Apiaceae) is represented by four species in Turkey. The composition of the essential oil of Opopanax genus members (Apiaceae) growing in Turkey was investigated in this study. GC-MS was used to analyze the composition of Opopanax essential oil samples that were taken from their natural environments. The Clevenger apparatus was used to hydrodistill the plant's aerial parts, and the yields were determined to be between 0.2% v/w (for O. siifolius) and 0.4% (for O. hispidus, O. chironium, and O. persicus). The results and the chemical data provided some information and clues on the chemotaxonomy of the genus Opopanax. In this study, ?-elemene, butanoic acid octyl ester, and cylopropane were the main compounds identified in the essential oils of O. chironium, O. hispidus, and O. persicus. In particular, hexynyl n-valerate was most abundant in the essential oil of O. chironium, cyclopropane in that of O. hispidus, ?-elemene in that of O. persicus, and n-hexadecanoic acid/palmitic acid in that of O. siifolius. In a chemotaxonomic approach, the essential oil analysis of the Opopanax species revealed that these species conformed in a cluster analysis with their morphological classification. The constituents of the essential oils of all examined in the genus Opopanax were determined in this study, which is the most thorough one to date. This study provides new information about the composition of the essential oils of the investigated species.
Keywords: Opopanax genus; essential oil; chemical composition; GC-MS